Matched-pair analysis of the impact of low-dose postoperative radiotherapy on prognosis in patients with advanced hypopharyngeal squamous cell carcinoma without positive surgical margins and extracapsular extension - Tao, Hengmin; Wei, Yumei; Shen, Zhong; Liu, Zhichao (Frontiers in Oncology, 2023)
We conducted a comparative analysis between low and high dose postoperative radiotherapy in patients with hypopharyngeal squamous cell carcinoma (HPSCC) in stage III or IV without positive surgical margins and extracapsular extension (ECE). Propensity Score Matching (PSM) was used to eliminate confounding factors and reduce bias.The matched-pair analysis included 156 patients divided into two groups: the low-dose radiotherapy group (LD-RT 50Gy, 78 cases) and the high-dose radiotherapy group (HD-RT 60Gy, 78 cases). Both cohorts were statistically comparable in terms of age, gender, subsite, and TNM classification.The median follow-up time was 49 months (ranging from 5 to 100 months). The overall survival rate (OS), progression-free survival rate (PFS), locoregional control rate (87% vs. 85.7%; P=0.754), distant metastases-free survival (79.2% vs. 76.6%; P=0.506), and the occurrence of second primary tumors (96.1% vs. 93.5%; P=0.347) showed no significant differences between the LD-RT group and the HD-RT group.The 3-year OS was 63% and 64.9% in the low-dose group and 61% in the high-dose group (P=0.547), respectively. The 3-year PFS was 63.6% and 54.5% (P=0.250), respectively, and the 3-year PFS of the entire group was 59.1%. Multivariate analyses revealed that pathological T, N classification, and pathological differentiation were associated with 3-year OS, PFS, and LRFS and were independent prognostic factors (P<0.05). LD-RT was not associated with an increased risk of death and disease progression compared to HD-RT.The results of postoperative low-dose radiotherapy did not show inferiority to those of high-dose radiation for patients with advanced hypopharyngeal cancer without positive surgical margins and ECE in terms of OS, PFS, locoregional control, and metastases-free survival.